2011
DOI: 10.1177/1352458511426816
|View full text |Cite
|
Sign up to set email alerts
|

EBV-specific immune responses in patients with multiple sclerosis responding to IFNβ therapy

Abstract: Clinically effective IFNβ therapy is associated with a reduction of proliferative T-cell responses to EBNA1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
1
16
0
2
Order By: Relevance
“…Our demonstration of significantly increased serological reactivity to EBNA-1 in the group of MS patients with disease activity during IFN-β therapy (IFNβ-non-responders) is in agreement with the findings from Farrell et al Further, the specific association between anti-EBNA-1 reactivity and disease activity is strengthened by a recent report from Comabella et al (2011) demonstrating a specific reduction in the proliferative T cell-mediated response to EBNA-1 during efficacious IFN-therapy. Our present demonstration of EBV EBNA-1 IgG as a relevant marker for disease activity, but not EBV EA IgM, or EBV EA IgG, is also in agreement with those reports.…”
Section: Discussionsupporting
confidence: 92%
“…Our demonstration of significantly increased serological reactivity to EBNA-1 in the group of MS patients with disease activity during IFN-β therapy (IFNβ-non-responders) is in agreement with the findings from Farrell et al Further, the specific association between anti-EBNA-1 reactivity and disease activity is strengthened by a recent report from Comabella et al (2011) demonstrating a specific reduction in the proliferative T cell-mediated response to EBNA-1 during efficacious IFN-therapy. Our present demonstration of EBV EBNA-1 IgG as a relevant marker for disease activity, but not EBV EA IgM, or EBV EA IgG, is also in agreement with those reports.…”
Section: Discussionsupporting
confidence: 92%
“…The MOA of IFN-b in MS is not clear but is thought to involve anti-inflammatory mechanisms. Nevertheless, IFN-b is known to inhibit the infectivity of EBV, cytomegalovirus (CMV), and other viruses, influence proliferative T cell responses to EBNA1 [68], and decrease the memory B cell compartment that is considered to be a pathogenic cell subset and key trigger in MS [69]. It is tempting to suggest that the MOA of IFN-b and other disease-modifying therapies (DMTs) [70] includes overlapping antiviral and anti-inflammatory mechanisms that support future simultaneous testing of MS drugs with divergent MOAs.…”
Section: Antiviral Compoundsmentioning
confidence: 99%
“…It is likely that such a strong reduction in the CD8+ T cell response to both viruses might due to the direct antiviral activity of the drug [41]. Recently, Comabella et al [50] reported that clinically effective IFN-β therapy is associated with downregulation of proliferative T cell responses to EBNA-1 without significant changes in the CD8+ T cell response against other (pooled) EBV antigens of the latent and lytic phase. Discrepancies with the present study could be due to technical issues, as discussed above.…”
Section: Discussionmentioning
confidence: 99%